Pengaruh Media Pembelajaran “Educaplay” terhadap Hasil Belajar Siswa dalam Konsep Sumber Energi dan Perubahannya di Kelas III SDN Brumbungan Lor - Iwing Ade Miranda; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
The purpose of this study was to understand the impact of using the digital educational tool Educaplay on student learning outcomes, specifically in learning the concept of energy sources and their transformations in third-grade students at Brumbungan Lor Elementary School. The main question examined was whether the use of this interactive platform significantly impacts student learning outcomes. The method used was a quantitative approach with a pre-experimental one-group pretest-posttest design. The subjects were all 17 third-grade students at Brumbungan Lor Elementary School. The research instrument consisted of a pretest and a posttest, consisting of 15 multiple-choice questions structured according to basic competencies regarding energy sources and their transformations. Data were analyzed using a paired sample t-test. The analysis showed a two-tailed significance value of 0.000, less than 0.05. This finding indicates that the null hypothesis (H0), which states there is no difference in learning outcomes before and after the treatment, is rejected. Conversely, the alternative hypothesis (H1), which states there is a significant difference after the treatment, is accepted. Thus, the study proves that the interactive learning media Educaplay has a significant impact on improving student learning outcomes. Students experienced improved understanding and academic achievement after participating in learning using this media. This demonstrates that technology integration, specifically Educaplay, can create engaging, interactive learning experiences and motivate students to be more active in the learning process. The final results of the study confirm that Educaplay is a suitable alternative learning media for improving student academic achievement. Therefore, educators and teachers are encouraged to utilize it as part of their learning strategies to support improved student learning outcomes.